ENU mutagenesis as a tool for understanding lung development and disease. (22nd July 2009) - Yates, Laura; McMurray, Fiona; Zhang, Youming; Greenfield, Andy; Moffatt, Miriam; Cookson, William; Dean, Charlotte
Abstract : ENU ( N -ethyl- N -nitrosourea) is a chemical mutagen that randomly induces point mutations in DNA. Since the 1990s ENU has been successfully used as a means to obtain mouse mutants using both gene-driven (reverse genetics) and phenotype-driven (forward genetics) approaches. A high-efficiency ENU approach results in approx. 25 functional mutations per genome; most of these will result in hypomorphic alleles. Our group has recently begun using ENU mutagenesis as a tool for understanding lung development and disease. In collaboration with other groups at MRC Harwell, we have undertaken a screen for recessive mutations affecting mouse lung development. We are currently pursuing two lines identified from this screen, Hel (head, eye and lung) and RecBA17 . Both these lines exhibit lung defects and we believe that by studying the phenotypes and identifying the causative mutations, we may also shed light on lung disease pathogenesis. In collaboration with Bill Cookson and Miriam Moffatt, we are also taking a gene-driven approach for understanding asthma. Using the Harwell ENU sperm archive, we have recovered mouse lines harbouring mutations in the asthma-susceptibility genes Phf11 (PHD finger protein 11) and Dpp10 (dipeptidylpeptidase 10). Functional analyses of these alleles are currently under way.